Tulkotâja lojalitâte 21. gadsimtâ: sociolingvistiks skatîjums - Silis, Janis (Kalbotyra, 2007)
In this article the author’s intention is to touch upon only some of the aspects characterizing translation as a sociolinguistic phenomenon relevant to translator’s faithfulness. Reduction of the scope of analysis is due to the fact that the problem of relations between translatology and sociolinguistics is considerably more extensive and therefore requires more detailed research producing a quantitatively much bulkier text. An attempt will be made to provide a rather impressionistic contrastive analysis of translation problems appearing in certain pairs of sociolinguistic correlations, such as source/target language and social group, source/target language and age group, as well as source/target language and gender. In the last two correlation pairs (and episodically elsewhere) translator as a representative of a definite age-bound or gender-bound social group will also be viewed. This method of analysis has successfully been used by the author in his previous publications on the subject (Sîlis, 1999 and 2006), as well as repeatedly applied by the authoritative sociolinguist Peter Trudgill (2001).The illustrative material used in the article comes from author’s own observations of problemsolving cases in translation and interpreting practice cases where Latvian is either the source or the target language, and similar instances analysed in research publications of other Latvian translation theorists.In the end of the discussion part the problem of culture-specific discrepancies of the SL and TL nations, reflected also in the difference of the respective culture of verbal expression, will also be tackled.